Cementless Oxford medial unicompartmental knee replacement: clinical and radiological results of 228 knees with a minimum 2-year follow-up - Panzram, Benjamin; Mandery, Mira; Reiner, Tobias; Gotterbarm, Tobias; Schiltenwolf, Marcus; Merle, Christian (Journal of Clinical Medicine, 2020)
(1) Background: Studies show several advantages of unicompartmental knee replacement (UKR) over total knee replacements (TKR), whereas registry based revision rates of UKR are significantly higher than for TKA. Registry data report lower revision rates for cementless UKR compared to cemented UKR. The aim of this study was to assess clinical and radiological results of cementless Oxford UKR (OUKR) in an independent cohort. (2) Methods: This retrospective cohort study examines a consecutive series of 228 cementless OUKR. Clinical outcome was measured using functional scores (Oxford Knee Score (OKS), American Knee Society Score (AKSS), Hannover Functional Ability Questionnaire for Osteoarthritis (FFbH-OA), range of motion (ROM)), pain and satisfaction. Radiographs were analyzed regarding the incidence of radiolucent lines (RL), implant positioning, and their possible impact on clinical outcome. (3) Results: At a mean follow-up of 37.1 months, the two and three year revision free survival-rates were 97.5% and 96.9%. Reasons for revision surgery were progression of osteoarthritis, inlay dislocation and pain. All clinical outcome scores showed a significant improvement from pre- to postoperative. The incidence of RL around the implant was highest within the first year postoperatively (36%), and decreased (5%) within the second year. Their presence was not correlated with inferior clinical outcome. Implant positioning showed no influence on clinical outcome. (4) Conclusion: Cementless OUKR showed excellent clinical outcome and survival rates, with reliable osteointegration. Neither the incidence of radiolucent lines nor implant positioning were associated with inferior clinical outcome.
Gesehen am 06.07.2020